Spy x family. 3 - Endō, Tatsuya, 1980- (Shonen Jump manga., 2020)
"Master spy Twilight is unparalleled when it comes to going undercover on dangerous missions for the betterment of the world. But when he receives the ultimate assignment--to get married and have a kid--he may finally be in over his head!... Twilight has overcome many challenges in putting together the Forger family, but now all his hard work might come undone when Yor's younger brother Yuri pops in for a surprise visit! Can Twilight outsmart Yuri, who actually works for the Ostanian secret service?!"--Provided by publisher.